Weekly profile of training load and recovery in elite rhythmic gymnasts - Debien, P.; Miloski, B.; Timoteo, T.; Ferezin, C.; Bara Filho, M. (Science of Gymnastics Journal, 2019)
The aim of this study is to analyze the weekly profile of internal training load (ITL) and recovery of elite rhythmic gymnasts during a season. Eight professional rhythmic gymnasts of the Brazilian senior group participated. The session rating of perceived exertion (session-RPE) and Total Quality Recovery (TQR) score were collected daily across a 37-week season. The session-RPE was collected after each session and the TQR before the first session of the day. The sum of ITL of each session of the day (dITL) and week (wITL), as well as average TQR scores, were retained for the analysis. Training monotony and strain were also recorded. For the analysis, the season was divided into preparatory period, competitive period and a period comprising the competition weeks, within the competitive period. The ITL and recovery profile were different between the days of the periods and the competition weeks. The competitive period as a whole showed higher mean wITL, dITL, and strain, and lower monotony than the others. However, during the competition weeks gymnasts presented the worst recovery and highest monotony scores, despite the lowest mean wITL and dITL. Negative correlation was found between dITL and TQR of the following day (r= -0.333; p<0.001). The ITL and recovery profile changed between the season periods and competition weeks. The training load profile of the competitive period and competition weeks did not guarantee good recovery, especially on the weekend. More variability in load magnitude is suggested, possibly including a day off, during competitive periods and competition weeks.